The Role of Green Accounting in Efforts to Prevent Environmental Pollution to Support Business Continuity : Peran Green Accounting Dalam Upaya Mencegah Pencemaran Lingkungan Untuk Menunjang Keberlangsungan Usaha - Ivanda Ilham; Heri Widodo (Academia Open, 2021)
This study aims to describe and explain the application of green accounting in helping business continuity at PT Petrokimia Gresik. This research is based on the fact that most companies are still less concerned about environmental pollution problems and only prioritize profits without paying attention to their surroundings and stakeholders. This research method uses qualitative, data collection is carried out by in-depth interviews, documentation of company reports or files that are directly related to environmental costs, then the last is observation. This is done by observing the state of the company to be studied. The data analysis method used interpretive analysis with testing the validity of the data (triangulation) and theory. The results of this study indicate that PT Petrokimia Gresik is still at a level that is not optimal in implementing the application of environmental costs (green accounting) in terms of identifying, recognizing, measuring and disclosing environmental costs for waste management. The company incurs costs regarding environmental conservation, but the company's treatment of these costs is still included in the factory overhead costs. Environmental costs must be reported separately, in the sense of being categorized alone rather than combining them with other costs. The company is still grouping it with other costs so that the environmental costs do not appear in the financial statements. As a result, the environmental costs are hidden.